Intertextuality as A Cultural Interaction Mechanism and Socio-Cultural Phenomenon - E P Shiniev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2010)
The article focuses on intertextuality as a concept associated with the tradition of postmodernism textology and a phenomenon of text interaction with the semiotic cultural environment. The concept of intertextuality emerges as an essential condition for the construction of meaning which includes the dialogical characteristics of the polylogue culture field. The author examines the evolution of intertextuality since M.M. Bakhtin up to contemporary theoreticians of postmodernism. The concept of intertextuality is the prominent characteristics of the contemporary «post» culture and the major channel of inter-cultural diffusion.